Biosorption of Pb2+ using Fusarium sp. RS01, a Hg2+ and Pb2+-resistant indigenous fungus of an abandoned illegal gold mining site - Risa Nofiani,; Rio,; Kiki Komalasari,; Puji Ardiningsih,; Santosa, Sri Juari (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to identify and characterize Hg2+ and Pb2+-resistant indigenous fungi that originated in Mandor, an abandoned illegal gold mining site in West Kalimantan, Indonesia. The resistant fungus which has the highest ability in uptaking Pb2+ is then further examined for its biosorption characteristics towards Pb2+. Three different samples consisted of samples taken in the sand area (RP), rhizosphere area (RR) and sediment area (RS) were collected as the sources of fungi. The three types of samples were inoculated in a potato dextrose agar (PDA) medium supplemented with 7.4 ppm of HgCl2 and 7.5 ppm of PbCl2 for screening Hg2+ and Pb2+-resistant fungi, respectively. Each screened fungus was identified macroscopically and microscopically. The tolerant index (TI) towards Hg2+ and Pb2+ was checked by measuring the fungal growth diameter in a PDA medium without or with the presence of different HgCl2 or PbCl2 concentrations. From six identified fungi, five of them showed resistance towards Hg2+ and Pb2+ to maximum concentrations of 200 ppm of HgCl2 and 2,085 ppm of PbCl2, respectively. The five identified fungi were Penicillium sp. RR01, Aspergillus sp. RR02, Aspergillus sp. RR03, Aspergillus niger RP01, and Fusarium sp. RS01. At the optimum condition of pH 6 and adsorption time 15 min, the application of 200 ppm of Fusarium sp. was able to remove 9.5 ppm of Pb2+. This Pb2+ biosorption followed well Freundlich isotherm model indicating that the Fusarium sp. RS01 had heterogenous active sites for the adsorption.